2012
DOI: 10.1159/000339317
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Gene Polymorphism Does Not Influence Clinical Phenotype and Response to Oral Contraceptive Pills in Polycystic Ovary Syndrome Women

Abstract: Aims: To assess whether a single nucleotide polymorphism (SNP50) of the aromatase gene (CYP19) is associated with polycystic ovary syndrome (PCOS) phenotypes and to investigate the influence of this polymorphism on the response of PCOS to treatment with oral contraceptive pills (OCP). Methods: 162 hirsute women were stratified into a classic PCOS group (hyperandrogenism, ovulatory dysfunction, c-PCOS) and an ovulatory PCOS group (hyperandrogenism, ovulatory cycles, polycystic ovaries, ov-PCOS). 51 women comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Additionally, certain promoter variants were independently associated with PCOS symptom score in UK adolescents [ 92 ]. The rs2414096 polymorphism lacked association with PCOS or with alterations in hormonal and metabolic variables after undergoing a 6-month treatment regime of oral contraceptives in both anovulatory and ovulatory PCOS women [ 93 ]. Another common polymorphism, a tetranucleotide repeat polymorphism (TTTA) n in the fourth intron related to suboptimal aromatase activity [ 94 ], has been investigated.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Additionally, certain promoter variants were independently associated with PCOS symptom score in UK adolescents [ 92 ]. The rs2414096 polymorphism lacked association with PCOS or with alterations in hormonal and metabolic variables after undergoing a 6-month treatment regime of oral contraceptives in both anovulatory and ovulatory PCOS women [ 93 ]. Another common polymorphism, a tetranucleotide repeat polymorphism (TTTA) n in the fourth intron related to suboptimal aromatase activity [ 94 ], has been investigated.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Whilst the pathogenesis of PCOS remains largely unknown, accumulating data suggest that PCOS is a complex disease which involves both genetic and environmental factors [3,4,5]. PCOS may begin in utero, because female mammals (rhesus monkeys, sheep, mice or rats) exposed to androgen in utero develop masculinized phenotypes similar to PCOS in adulthood [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies detailed in Table 4 , failed to detect gene-drug interactions, but they confirmed therapies efficiency in terms of body composition, endocrine, metabolic and ovulation improvements ( 95 , 96 , 101 , 102 , 108 110 ). Besides, ovulation predictors such as high FSH levels and low BMI range were identified ( 97 ).…”
Section: Pharmacogenomics In Pcosmentioning
confidence: 95%
“…After 6 months of OCP treatment, testosterone, glucose, and LH levels were reduced, and hirsutism improvements were seen. However a slight increase of lipids was also detected ( 101 , 102 ). OPC have potential adverse effects on IR, diabetes mellitus and coagulability ( 89 ), indeed Maier et al.…”
Section: Pharmacogenomics In Pcosmentioning
confidence: 98%